PENGARUH PENERIMAAN PAJAK KENDARAAN DAN BEA BALIKNAMA TERHADAPPENDAPATAN ASLI DAERAH PROVINSI SUMATERA SELATAN - Periansya Diah Elvina Desi Indriasari (JURNAL RISET TERAPAN AKUNTANSI, 2017)
This study aims to analysis the effect of Vehicle Tax (PKB) and VehicleTransfer Tax (BBNKB) to Regional OwnSource Revenue (PAD) in South Sumatera Province. The data used are time series data for the period of 2013-2016 which is presented monthly from January to December, using documentation method done at Regional Revenue Board (Bapenda) of South Sumatera Province. Sample in this research using samples saturated. The results of this study indicate that partially PKB variable positively and significantly influence to PAD in South Sumatera Province year 2013-2016, while variable of BBNKB have no significant influence to PAD in South Sumatera Province year 2013-2016, and simultaneously PKB and BBNKB positively and significantly influence to PAD in South Sumatera Province in 2013-2016.